A QI initiative for bridging the health literacy gap by Educating internal medicine residents at a community hospital. Issue 5 (3rd September 2018) - Wahab, Ahsan; Ali, Ahmad; Nazir, Sarah; Ochoa, Lisa; Khan, Hafiz; Khan, Mahin; Chaudhary, Siddique; Smith, Susan J.
ABSTRACT: Introduction : Only 12% of Americans have proficient health literacy (HL). Patients hide this fact from others including physicians. This quality improvement (QI) project was developed to compare internal medicine (IM) resident physicians' (RPs) ability to accurately predict patients with low HL and to improve IM-RPs' understanding of low HL and its impact on patients. Aim statement : Over six-months, our aim was to increase the IM residents' HL-knowledge by 30% as measured by an HL-Knowledge-Based-Survey. Methods : After IRB exemption, patients visiting the residency-clinic within a two-week period were screened for low HL with the REALM-R, a validated tool. Post-visit, IM-RPs were asked to predict their patients' HL. A comparison of predicted-HL and measured-HL was made. IM-RPs were emailed an HL-Knowledge-Based-Survey (pre-education and post-education) to measure their background knowledge of HL. Education included HL-workshop, pre-clinic conference and lectures. Pre-education and post-education scores were compared. Results : HL-RPs' prediction and patients' REALM-R results were completed by 108 RP-patient pairs. IM-RPs correctly identified 5 of 40 patients who were at risk for low HL (sensitivity = 12.5%). They correctly identified 97.1% of 68 who were not at risk (specificity = 97.1%). Our residents' knowledge pre-education and post-education did not improve – 58% (n = 18) vs 62% (n = 10). Conclusion : Our QI result verified that IM-RPs overestimate patients' HL and do not understand the magnitude or consequences of low HL nor techniques to improve such patients' understanding. This suggests an area for residency curricular development in order to improve patients' ability to navigate the healthcare system successfully.